Inconsequential female autonomy in misogynic hate communication: male dominance, dehumanization, and sexualization in digital collaborative storytelling - Krug, Maximilian (Frontiers in Communication, 2025)
This paper explores the construction of masculinity and femininity in misogynic hate communication through the lens of Membership Categorization Analysis, focusing on language use and the interrelations of sexuality, violence, and power dynamics in collaborative storytelling. Analyzing German-language online interactions where male participants role-play both male and female characters, the study examines how gendered narratives are co-constructed and maintained. Findings indicate that male characters’ responses are largely unaffected by female autonomy assertions, suggesting a disregard for female agency, as male mistreatment appears consistent regardless of female actions. However, significant associations were found between male dominance assertion and dehumanizing language, as well as between sexualized language and scenes involving power struggles, highlighting a thematic connection between sexuality, control, and dehumanization in reinforcing gendered hierarchies. The findings contribute to a deeper understanding of misogynic communication, revealing how linguistic practices support toxic masculinity and perpetuate gender inequality, with implications for digital policy and moderation strategies aimed at fostering inclusivity in online spaces.